Application of compulsion is in criminal realization in the conditions of democratic society - Назаров, Віктор Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article the questions of mechanism of state compulsion are investigational at investigation of crimes, the norms of international law and national legislation are generalized in relation to legality of applicationof force the proper public servants which provide maintenance of law and order. The problem aspects of application of measure of judicial compulsion as detention are considered.